Mechanical beast and where to find them / Hasnul Azwan Azizan - Azizan, Hasnul Azwan (Faculty of Art and Design, 2021)
The 20th century has left us a long time ago but it gave significant accomplishment to the advancements in human technological history. Over and over again technology and the human spirit seem to be intertwined in fate and destiny. Sought to be just mere tools in giving society the edge it needed to live and survive has become more “conscious’ as people describe it in the modern life. The Beast of mythology may very well be forgotten and honoured as relics of the past but the presence of mechanical manifest is always here and keep on evolving to the very best of people‘s attention. The series of where to find mechanical existence is to explore the human condition of relying, adapting, embracing or even revolting at the sight of mechanical entity surrounding them. This process could be defined by a slur of coined terms and academic terminologies but it is the essence which is more important to be realized that we have lived and always live in a pseudo mechanical environment, everything from washing to cars and aeroplanes which have some or plenty of moving parts which are controlled by an operator.